Ultra-thin V2O5 nanosheet based humidity sensor, photodetector and its enhanced field emission properties - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
We report the synthesis of V2O5 nanosheets by a simple hydrothermal method. The as synthesized V2O5 nanosheets were characterized by Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and UV-Vis spectroscopy. The humidity sensing behaviors were investigated in the range of 11-97% relative humidity (RH) at room temperature. The maximum sensitivity of 45.3%, response time of similar to 4 min and recovery time of similar to 5 min were observed for the V2O5 nanosheet based sensor. We also demonstrated the V2O5 nanosheets as an ultra-violet photodetector with a sensing response time of similar to 65 s and recovery time of similar to 75 s with a maximum photoresponsivity of similar to 6.2%. Further, we have also carried out field emission (FE) investigations of V2O5 nanosheets under a planar ``Diode'' assembly in an ultrahigh vacuum (UHV) chamber at a base pressure of similar to 1 x 10(-8) mbar. The turn on fields required to draw field emission current densities of 1 mu A cm(-2) and 10 mu A cm(-2) are found to be 1.15 V mu m(-1) and 1.72 V mu m(-1), respectively. We achieved a maximum field emission current density of 1.532 mA cm(-2) at an applied electric field of 3.2 V mu m(-1). The field enhancement factors calculated from the slope of the Fowler-Nordheim (F-N) plot are found to be 8530 and 3530 at low field and high field regions, respectively. Our results open up several avenues towards the successful utilization of V2O5 nanosheets and other metal oxide nanosheets for various nanoelectronics device applications including sensors, photodetector and flat panel displays.

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Humidity sensing and photodetection behavior of electrochemically exfoliated atomically thin-layered black phosphorus nanosheets - Erande, Manisha B.; Pawar, Mahendra S.; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2016)
Recent investigations on two-dimensional black phosphorus material mainly highlight work on few atomic layers and multilayers. It is still unknown if the black phosphorus atomically thin sheet is an ideal structure for the enhanced gas solid interactions due to its large surface area. To further investigate this concern, we have synthesized few atomic layer thick nanosheets of black phosphorus using an electrochemical exfoliation method. The surface morphology and thickness of the nanosheet were identified using AFM, TEM, and Raman spectroscopy. The black phosphorus nanosheet thick film device was used for the gas sensing application with exposure to different humidites. Further, the few layer black phosphorus nanosheet based transistor shows good mobility and on/off ratio. The UV light irradiation on the black phosphorus nanosheet shows good response time. The overall results show that the few layer thick film of black phosphorus nanosheets sample exhibits creditable sensitivity and better recovery time to be used in humidity sensor and photodetector applications.
Keywords: black phosphorus; electrochemical exfoliation; humidity sensor; photodetector

Large area chemical vapor deposition of monolayer transition metal dichalcogenides and their temperature dependent Raman spectroscopy studies - Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; Late, Dattatray J. (Nanoscale, 2016)
We investigate the growth mechanism and temperature dependent Raman spectroscopy of chemical vapor deposited large area monolayer of MoS2, MoSe2, WS2 and WSe2 nanosheets up to 70 mu m in lateral size. Further, our temperature dependent Raman spectroscopy investigation shows that softening of Raman modes as temperature increases from 80 K to 593 K is due to the negative temperature coefficient and anharmonicity. The temperature dependent softening modes of chemical vapor deposited mono-layers of all TMDCs were explained on the basis of a double resonance phonon process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other emerging two-dimensional layered and heterostructured materials.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

Temperature-dependent Raman spectroscopy and sensor applications of PtSe2 nanosheets synthesized by wet chemistry - Pawar, Mahendra S.; Late, Dattatray J. (Beilstein Journal of Nanotechnology, 2019)
We report on a wet chemistry method used to grow PtSe2 nanosheets followed by thermal annealing. The SEM and TEM analysis confirms the formation of PtSe2 nanosheets. Furthermore, XRD, Raman, XPS and SAED patterns were used to analyze the crystal structure and to confirm the formation of the PtSe2 phase. The temperature-dependent Raman spectroscopy investigations were carried out on PtSe2 nanosheets deposited on Si substrates in the temperature range 100-506 K. The shifts in Raman active E-g and A(1g) modes as a function of temperature were monitored. The temperature coefficient for both modes was calculated and was found to match well with the reported 2D transition metal dichalcogenides. A PtSe2 nanosheet-based sensor device was tested for its applicability as a humidity sensor and photodetector. The humidity sensor based on PtSe2 nanosheets showed an excellent recovery time of approximate to 5 s, indicating the great potential of PtSe2 for future sensor devices.
Keywords: nanosheets; PtSe2; Raman spectroscopy; Sensor; thermal effect

MoS2 and CdMoS4 nanostructure-based UV light photodetectors - Pawar, Mahendra S.; Kadam, Sunil R.; Kale, Bharat B.; Late, Dattatray J. (Nanoscale Advances, 2021)
We have developed MoS2 nanosheets and CdMoS4 hierarchical nanostructures based on a UV light photodetector. The surface morphologies of the as-prepared samples were investigated via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The performance parameters for the present photodetectors are investigated under the illumination of UV light having a wavelength of similar to 385 nm. Upon the illumination of UV light, the CdMoS4-based photodetector device showed a better response to UV light compared to the MoS2 device in terms of photoresponsivity, response time (similar to 72 s) and recovery time (similar to 94 s). Our results reveal that CdMoS4 hierarchical nanostructures are practical for enhancing the device performance.